Pengawasan Kepala Sekolah tentang Kedisiplinan Guru di MTs Ilham Palembang - Ibrahim, Ibrahim; Niswah, Choirun; Ramlah, Putri Maharany (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to understand how the supervision of the school principal regarding teacher discipline is carried out at mts Ilham Palembang. The research subjects consist of monitoring, inspection, guidance, punctuality, work process compliance, and work results compliance. This research is a qualitative descriptive study, and the research subjects include three individuals, namely the school principal, the vice principal in charge of the curriculum, and the teachers. Data is collected through three methods: interviews, observations, and documentation. The data analysis technique involves data collection, data presentation, and data verification. The research findings indicate that: (1) Monitoring is carried out by supervising teachers while they are teaching in the classroom. (2) Inspection involves structured examinations of teachers and their attendance. (3) Guidance includes planning, discussion, and evaluation meetings related to teacher discipline. (4) Punctuality entails checking the teachers' punctuality according to the established schedule. (5) Work Process Compliance involves the principal monitoring a teacher's work process according to the schedule and the implementation plan. (6) Work Results Compliance consists of the principal consistently appreciating teachers who adhere to their work results and evaluating any mistakes in the work process